Exploring learner to institutional factors and learner characteristics as a success factor in distance learning - Amoozegar, Azadeh; Mohd Daud, Shaffe; Mahmud, Rosnaini; Ab. Jalil, Habibah (Timeline Publication, 2017)
In spite of dramatic increase of online courses and student enrollment, there are many indications that online courses are unsuccessful at meeting students’ needs and students are dissatisfied with their online course experiences, which brings about a serious concern regarding the dropout rates of online courses. For solving this issue, it is crucial that researchers identify and study the factors that lead to student satisfaction with online courses because course satisfaction is considered to be the largest determinant in reducing dropout in distance learning environment. Hence, the purpose of this study is to identify factors contributing to course satisfaction among distance learners in Malaysian research universities. These factors are categorized into institutional factors (administrative support, technology support and university support), learner characteristics (motivation, self-regulated learning and selfefficacy). In this study, all variables were selected based on the social presence and transactional distance theory and on previous studies on satisfaction of students. Researchers used quantitative research where data were collected through questionnaires among 367 distance-learning undergraduate students. The findings indicated a statistically significant relationship between institutional factors and learner characteristics toward course satisfaction. The study suggested that learners with high level of self-efficacy have better academic performance in the distance-learning programs and are more likely to be more engaged in their learning.